MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN IPA KELAS V DI SDN 15 LIMBOTO BARAT KABUPATEN GORONTALO - Nurain Manono; Thamrin A. Kum; Yane Hardiyanti Mahmud (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
The aim of research is to improve student learning outcomes through the application of contextual learning models in science subjects in class V at SDN 15 Limboto Barat. The method used classroom action research with research subjects namely 34 class V students. This research was carried out in the form of a cycle and each cycle consists of 4 stages, namely the planning stage, implementation stage, observation and reflection stage. This research shows student learning outcomes throughout the research implementation have increased. This is shown by the low learning outcomes at the time of initial observation reach 41.18% in the poor category. After taking action, the learning outcomes in cycle I were 67.64% in the quite good category. In cycle II it increased by 94.11% with a very good category according to KKM ≥70. Thus, the action hypothesis which asks if teachers use a contextual learning model, then student learning outcomes in Class V science subjects at SDN 15 Limboto Barat can increase, is relatively acceptable. Having achieved the provision of actions from cycle I to cycle II, the researcher ended the meeting in cycle II, the second meeting, because it had met the predetermined performance indicators, namely ≥ 80%.